2019
DOI: 10.1159/000496990
|View full text |Cite
|
Sign up to set email alerts
|

Early Unclamping Laparoscopic Partial Nephrectomy for Complex Renal Tumor: Data from a Chinese Cohort

Abstract: Objective: To evaluate the efficacy and safety of early unclamping laparoscopic partial nephrectomy (LPN) for complex renal tumor relative to the standard artery clamping technique (SCT). Methods: Sixty-one patients with complex renal tumor (RENAL score ≥7) underwent LPN at our institution from January 2013 to April 2017. LPN was performed via SCT in 32 patients and via the early unclamping technique (EUT) in 29 patients. Operation time, warm ischemia time (WIT), blood loss, bleeding requiring transfusion, tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Tumor complexity, one of the important determinants of surgical and oncological outcomes, deeply impacts the decision of surgical approach . Several studies have demonstrated the safety and feasibility of minimally invasive PN for complex renal tumor, especially for complex T1a renal tumors . RPN has been considered as a feasible option in management of ≥4 cm renal tumors with moderate or high nephrometry scores as well .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor complexity, one of the important determinants of surgical and oncological outcomes, deeply impacts the decision of surgical approach . Several studies have demonstrated the safety and feasibility of minimally invasive PN for complex renal tumor, especially for complex T1a renal tumors . RPN has been considered as a feasible option in management of ≥4 cm renal tumors with moderate or high nephrometry scores as well .…”
Section: Discussionmentioning
confidence: 99%
“…Several centers in China and abroad have successively reported the clinical application of early unclamping technique. Zhang et al [13] reported 29 cases of laparoscopic partial nephrectomy with early unclamping. The results showed that the mean warm ischemia time was 13.4 min, signi cantly lower than 21.1 min in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Several centers in China and abroad have successively reported the clinical application of the early unclamping technique. Zhang et al [ 18 ] reported 29 cases of laparoscopic partial nephrectomy with early unclamping. The results showed that the mean warm ischemia time was 13.4 min, which was significantly lower than 21.1 min in the control group.…”
Section: Discussionmentioning
confidence: 99%